Analisa Rasio Keuangan terhadap Pergerakan Harga Saham pada Perusahaan Sektor Properti Periode 2017-2020 - Johny Budiman; Gusfandi Gusfandi (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study discusses the issue of various factors that affect the stock price of a company. The research focused on the property company sector in Indonesia which has been listed and has financial statements on the Indonesia Stock Exchange from January 2017-December 2020 using time series data collection techniques. The method used in this study is a deductive analysis that utilizes the Eviews version 12 application with data processing techniques in the form of data quality tests (chow test, hausman test and lagrange multiplier test) and panel data analysis test (t test, F test, and coefficient of determination test). The results of the study concluded that the ratio of total assets turnover is significantly positive having an impact on the share price; the rate-of-return ratio of assets is significantly negative in having an impact on stock prices. The exchange rate ratio, earnings per share and debt to equity ratio do not significantly have an impact on stock prices.